PENGARUH PENGGUNAAN JENIS GULA TERHADAP KUALITAS KUE SARANG SEMUT - Jannah, Raudhatul; Faridah, Anni; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was motivated by the only type of sugar that had been used in making sarang semut cake. The absence of the use of different types of sugar that affect the quality of the sarang semut cake. The use of sugar mommonly applied is granulated sugar. The purpose of this reserch to analyze the effect of using of the kind of sugar for quality of sarang semut cake that incude the volume, shape, color, smell, texture and taste. This tpye of research pure experiment with complete random plan method. The variabel of research include free variabel that is XO (sugar), X1(aren sugar), X2 (palm sugar), and X3 (lump sugar). Primary data that sourced from 30 semi trained panelists by proposed organoleptic test format. Data analyst with ANAVA, if the result show the real difference then continued by Duncan test. The result of reseacrh is there are a real difference by using the kind different types of sugar at color quality, smooth texture, uniforming of shape, chewy texture, and the taste that have not real difference. The best kind of sugar of making sarang semut cake are the using of palm sugar for coor indicator, hollow texture and taste.Keywords: Effects, The type of sugar, Quality, Sarang Semut Cake